Masculine-feminine: Implications of the abundance of hair on gender perception - Bouzas Loureiro, Nuria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
Hair is an element that has been present in human evolution since time immemorial. The excessive growth of hair on the body starts from a historical reality, since they are the result of real diseases: hypertrichosis and hirsutism. Taking as a starting point the image of the bearded women, we will address the stereotypes about female sexuality, the ideals of beauty and the definition of gender that are taken up in the creation of contemporary works of art in which the absence or presence of hair and its body location is a decisive element.